Influence of infectious factors on changes in hormonal indicators in women in the early period of miscarriage - Oybekovna, Muхitdinova Kamola; Aleхseevich, Aleinik Vladimir; Mihaylovna, Babich Svetlana; Nabievna, Negmatshaeva Xabiba; Azimovna, Zhuraeva Mohigul (Linguistics and Culture Review, 2021)
The work studied the influence of infectious factors on changes in immunological and hormonal parameters in women who have a full pregnancy without infections of the genitourinary system and women with an infection of the genitourinary system and have miscarriages in the early stages of up to 12 weeks of pregnancy. It was concluded that in women in early pregnancy, the presence of infections of the genitourinary system, with insufficient corrective effect of protease inhibitors and TGF-?1. The formation of a pronounced pro-inflammatory immune response is possible, which can contribute to an imbalance of sex hormones. It manifests itself in a slight decrease in prolactin, FSH, LH, but at the same time a pronounced and reliable decrease in the value of progesterone and an increase in the level of estradiol. Thus, all this can contribute to the unfavorable course of early pregnancy and the development of miscarriages.